1987
DOI: 10.1016/0378-1119(87)90262-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the genome of human spumaretrovirus

Abstract: SUMMARYDNA ofhuman spumaretrovirus (HSRV) was cloned from both cDNA and from viral DNA into phage A. and bacterial plasmid vectors. The recombinant plasm.ids harboring viral DNA were characterized by Southem blot hybridization and restriction mapping. Physical maps were constructed from cDNA and found to be colinear with the restriction maps obtained from viral DNA. The recombinant clones isolated contained viral DNA inserts which rangein size from 2.2 kb to 15.4 kb. The recombinant clones allowed to construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Virus-specific DNA fragments were prepared from recombinant clones pHSRV-H-C55 and pHSRV-E-D 2 (Flfigel et al, 1987;Rethwilm et al, 1987). These fragments were Css (the HindlII insert covering the 3' part of the pol, env and bel genes), Css-hh (the 688 bp HinpI fragment schematically shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Virus-specific DNA fragments were prepared from recombinant clones pHSRV-H-C55 and pHSRV-E-D 2 (Flfigel et al, 1987;Rethwilm et al, 1987). These fragments were Css (the HindlII insert covering the 3' part of the pol, env and bel genes), Css-hh (the 688 bp HinpI fragment schematically shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Three of these genes called bel 1, 2 and 3 are located between the env gene and the 3' long terminal repeat, whereas the fourth one, $1, is found between thepol and env genes (Fliigel et al, 1987;. From the nucleotide sequence data (Fliigel et al, 1987;Rethwilm et al, 1987;, HFV env-encoded proteins of 102K, 54K and 47K in their unglycosylated forms would be predicted.…”
Section: Kai-olaf Netzer Axel Rethwilm* Bernd Maurer and Volker Termentioning
confidence: 99%
“…A TATA box motif was identified from 226 to 221 in the LTR. Sequence comparison with the PFV Tas responsive element (TRE) (Rethwilm et al, 1987) revealed a highly conserved sub-sequence from 247 to 258. A splice-donor sequence was found in the R region, defining exon one as 51 nt.…”
mentioning
confidence: 99%